Cita Hidup Bebas Dari Belenggu Pesimisme Di Masa Penjajahan Dalam Pandangan Amal Hamzah - Nadifa Ma Hira; Dyah Pratiwi (Politeknik Kampar, 2023)
Literary works during the Japanese colonial era would certainly be a history in literature in Indonesia. For three and a half years the Japanese gave birth to literary works which not only served as a medium of communication for the audience, but also as an expression of the writers who created them. The subject of this paper is to get to know more about the ideals of free life in the colonial period in literary works created by Amal Hamzah. This research reveals Amal Hamzah’s attitude, contradictions, and views regarding life concerns faced by his nation during Japan. Literary works serve as a government propaganda tool to gain sympathy from the people of Indonesia. This invites the pros and cons of the literary community itself. Not all literary works are a propaganda tool of the government because their contens are in the form of criticism of the Japanese government. This makes literary works whose tone refuses to be removed and only circulated among limited groups, even published after independence.